46-Year-Old Man with Bilateral Metachronous Pleomorphic Adenoma of the Parotid Gland (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: pleomorphic adenoma; bilateral; metachr-onous; parotid gland